2017
DOI: 10.1016/j.canlet.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

GOT1-mediated anaplerotic glutamine metabolism regulates chronic acidosis stress in pancreatic cancer cells

Abstract: The increased rate of glycolysis and reduced oxidative metabolism are the principal biochemical phenotypes observed in pancreatic ductal adenocarcinoma (PDAC) that lead to the development of an acidic tumor microenvironment. The pH of most epithelial cell-derived tumors is reported to be lower than that of plasma. However, little is known regarding the physiology and metabolism of cancer cells enduring chronic acidosis. Here, we cultured PDAC cells in chronic acidosis (pH 6.9~7.0) and observed that cells cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…It would be interesting to establish if GOT1 knocked-down PC3 and LNCaP cells are more sensitive to ROS-inducing treatments such as ionizing radiation. In PDAC, GOT1 plays a role in anaplerotic metabolism countering ROS production in low pH conditions 53 . However, this is unlikely to be the case in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to establish if GOT1 knocked-down PC3 and LNCaP cells are more sensitive to ROS-inducing treatments such as ionizing radiation. In PDAC, GOT1 plays a role in anaplerotic metabolism countering ROS production in low pH conditions 53 . However, this is unlikely to be the case in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…The end result is increased reducing potential of the cell in the form of NADPH [66]. In a related manner, it has been recently reported that cell survival in the acidic TME imparted by lactate production from elevated glycolysis relies on increased expression of GOT1 and the aforementioned non-canonical glutamine pathway [67]. Considering that KRAS shunts glucose carbon from glycolysis away from the oxidative, NADPH generating branch of the PPP, the GOT2-GOT1-ME1 pathway becomes a major source of cytosolic NADPH production.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells exhibit metabolic properties distinct from normal cells in order to adapt to the nutritional needs for the proliferation (79). Cancer cells are more dependent on aerobic glycolysis, fatty acid synthesis, nucleic acid synthesis, and glutamine metabolism (7, 1012). However, the therapeutic efficacy of targeting the metabolic enzymes in improving the therapeutic resistance and the mechanism by which enzymatic inhibition can overcome the therapeutic resistance is not fully understood.…”
Section: Introductionmentioning
confidence: 99%